NILAI MORAL DALAM STRUKTUR NOVEL ANDREA HIRATA: KAJIAN STRUKTURALISME GENETIK - Andri Wicaksono; Siti Rukiyah; Ridwan Ridwan (Fakultas Teknik Universitas Negeri Makassar, 2026)
This study aims to describe and analyze moral values within the structure of the novels Laskar Pelangi and Padang Bulan by Andrea Hirata. This research employs a qualitative approach using content analysis methods and the genetic structuralism perspective. The research data consist of words, sentences, dialogues, and narration containing moral values in the novels. Data collection techniques were carried out through intensive reading and data recording. Data analysis techniques were conducted through stages of data reduction, classification, interpretation, and drawing interpretive conclusions by linking the intrinsic structure of the text and social context through the genetic structuralism framework. The results indicate that moral values are constructed through the intrinsic elements of the novel, namely theme, plot, and characterization. The findings of this study show that moral values in the novels are not normative, but rather constitute a narrative construct representing the collective consciousness of society. Thus, literary works have the potential to serve as reflective media in character education and the teaching of Indonesian Language and Literature. The implications of these results indicate that literary analysis based on genetic structuralism can be used as a reflective approach in literature teaching, particularly in the development of character education based on narrative understanding. In addition, the integrative model between intrinsic structure and moral values can serve as a methodological alternative in Indonesian literary research.